Methods and techniques of public consultation - Brzeziński, Kamil; Kretek-Kamińska, Agnieszka; Krzewińska, Aneta; Zając, Julia (Lodz University Press, 2024)
The problems faced by individuals responsible for conducting social consultations are quite common, regardless of the consultation’s subject, the type of institution or the locality organizing it. This publication describes these problems and proposes solutions. The authors are sociologists specializing in the methodology of social research, with experience in planning and conducting consultations and analyzing their results in collaboration with local governments, state institutions, non-governmental organizations, universities, cultural institutions, and informal groups. Readers interested in the issues of social consultations will receive not only practical guidance on specific consultation tools, but also an explanation of why certain actions are better performed in a particular way. An additional advantage is a meta-analysis of consultation methods and techniques, as well as a review of examples of innovative and common practices. All of this is filtered through methodological rules. The authors do not only present various consultation techniques and tools, but also propose a new classification of these techniques, grouping them based on several essential dimensions: the way consultation participants’ statements are recorded and the nature of the conclusions drawn, standardization of procedures, requirements for organizers and participants, relations between them, or consultation procedures. Although practitioners of consultations can benefit from this book, it still maintains a scientific character. The discussed issues are approached systematically, methodically, critically and comprehensively, serving as an impetus for scientific reflections, in-depth studies, or research projects.